Indeks Glisemik Umbi-Umbian - Yustinus Marsono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
A new approach based on glycemic index was suggested in selecting foods for the diabetes patients. A study on glycemic index of selected tuber foods has been conducted to provide Glycemic Index (GI) of the foods. The tubers including Taro (Xanthosoma violaceum SCHOOT), Yam (Dioscorea aculeata LINN), edible canna (Canna edulis KER), arrowroot (Maranta arundinacea LINN) and sweet potato (Ipomoea balatas POIR) were selected. The foods were analyzed for total sugar and starch after streaming. Ten volunteers (21-23 years old) of the nurse's students of the Panti Rapih Hospital Yogyakarta were provided. They took a night fasting and the blood sample was taken in the next morning. The food tested was given and blood sample was taken at 30, 60, 90 and 120 minutes after meal. Glucose level of the blood was measured and drawn graphically. GI was measured as the area under the postpradial blood glucose curve for a food expressed as a percentage of the area after the consumption of reference food ( bread). The food tested and the reference food contains 50-g available carbohydrate, except for arrowroot and it reference contains 25-g available carbohydrate. It was found that tubers investigated contain 58-76% starch and 1.5-21 % total sugar. Protein and fats varied 3-8% and 0.06-1.45% respectively. With bread as reference food, Glycemic Index of food investigated varied from 14 (arrowroot) to 179 (sweet potato). GI of taro, yam and edible were 95, 90 and 105, respectively.